2016
DOI: 10.1002/smj.2466
|View full text |Cite
|
Sign up to set email alerts
|

Who cooks the books in China, and does it pay? Evidence from private, high‐technology firms

Abstract: Research summary: We document the extent of fraudulent reporting among 467 private Chinese technology companies. Comparing the financial statements concurrently submitted to two different state agencies, we demonstrate a systematic gap in reported profit figures in the two sets of books. We find: (1) more than half the sampled companies report incentive‐compatible, materially discrepant profit numbers to the two agencies; (2) politically connected companies are approximately 18 percent more likely to commit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 64 publications
(77 reference statements)
0
44
0
Order By: Relevance
“…The idea that individuals tend to be consistent in their risk preferences enjoys broad support-some individuals simply seem more comfortable incurring risks than others (Bromiley & Curley, 1992;Dohmen et al, 2011;Sitkin & Weingart, 1995). Risk assessments based on incentivized behavioral tasks should therefore offer a powerful though still underutilized method for behavioral strategy research (Powell et al, 2011).…”
Section: Managerial Risk Preferencesmentioning
confidence: 99%
“…The idea that individuals tend to be consistent in their risk preferences enjoys broad support-some individuals simply seem more comfortable incurring risks than others (Bromiley & Curley, 1992;Dohmen et al, 2011;Sitkin & Weingart, 1995). Risk assessments based on incentivized behavioral tasks should therefore offer a powerful though still underutilized method for behavioral strategy research (Powell et al, 2011).…”
Section: Managerial Risk Preferencesmentioning
confidence: 99%
“…This is especially true for state‐owned enterprises and state‐linked enterprises, which dominate the heavy manufacturing and resource extraction industries. Some research has shown that such connections are important to doing business in China, but that they can also lead to self‐dealing and other ethical violations (Stuart and Wang ). Indeed, Stuart and Wang concluded in their paper that ‘it pays to cheat’.…”
Section: Advancing Theory On Interlocking Directoratesmentioning
confidence: 99%
“…However, fraud can only be observed when fraudsters are punished. Past studies only consider detected fraud rather than the underlying population of all fraudulent activities (Stuart and Wang, 2016). In this study, the probability of detected fraud is considered to be the product of two latent probabilities: the probability of fraud commission and fraud detection.…”
Section: Introductionmentioning
confidence: 99%